2019
DOI: 10.1039/c8ra09618j
|View full text |Cite
|
Sign up to set email alerts
|

4-(Pyridin-4-yl)thiazol-2-amine as an efficient non-toxic inhibitor for mild steel in hydrochloric acid solutions

Abstract: The corrosion inhibition performance and mechanism of 4-(pyridin-4-yl)thiazol-2-amine toward mild steel in hydrochloric acid were studied for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The chemical structure of organic molecules, surface charge distribution and corrosive medium would have an influence on the adsorption process. The plots of C inh /θ versus C inh for PPAPO in the concentration range 1 to 10 mM at 333 K yielded a straight line with correlation coefficient value 0.9724 (figure 7), suggesting that the adsorption of PPAPO obeys the Langmuir adsorption isotherm represented by the following equation (3.6) [25,26]:…”
Section: Adsorption Isothermmentioning
confidence: 91%
“…The chemical structure of organic molecules, surface charge distribution and corrosive medium would have an influence on the adsorption process. The plots of C inh /θ versus C inh for PPAPO in the concentration range 1 to 10 mM at 333 K yielded a straight line with correlation coefficient value 0.9724 (figure 7), suggesting that the adsorption of PPAPO obeys the Langmuir adsorption isotherm represented by the following equation (3.6) [25,26]:…”
Section: Adsorption Isothermmentioning
confidence: 91%
“…It can also be seen from the anodic polarization curve that DEEQ has an evident inhibitory effect on the mild steel electrode at a lower anode potential, which is related to the adsorption of DEEQ on the surface of the mild steel electrode and the formation of a protective layer of inhibitor. 10,38 However, when the polarization potential continues to increase, it can be observed that the curves are close to coinciding. This may be due to the rapid dissolution of mild steel at the strong polarization potential, which causes the desorption of DEEQ from the electrode's surface.…”
Section: Weight Loss Measurementsmentioning
confidence: 90%
“…Therefore, adding a corrosion inhibitor is an economical and effective method that has received increasing attention. 6,7,38 According to the chemical composition, a corrosion inhibitor is divided into two parts: an inorganic portion and an organic inhibitor. The organic inhibitor molecules contain a highly electronegative polar group (O, N, S, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The use of thiazole derivatives as corrosion inhibitors has been discussed in several publications [37][38][39][40][41][42]. Table 4 shows the protection efficiency and ΔG ads obtained of some thiazole derivatives exploited as corrosion inhibitors of steel in a 1 M HCl medium.…”
Section: Adsorption Isothermmentioning
confidence: 99%